Net zeros and ones how data erasure promotes sustainability, privacy, and security - Stiennon, Richard, 1959-; Ernst, Russ B.; Forslund, Fredrik (John Wiley & Sons, Inc., 2022)
Design, implement, and integrate a complete data sanitization program In Net Zeros and Ones: How Data Erasure Promotes Sustainability, Privacy, and Security, a well-rounded team of accomplished industry veterans delivers a comprehensive guide to managing permanent and sustainable data erasure while complying with regulatory, legal, and industry requirements. In the book, you'll discover the why, how, and when of data sanitization, including why it is a crucial component in achieving circularity within IT operations. You will also learn about future-proofing yourself against security breaches and data leaks involving your most sensitive information--all while being served entertaining industry anecdotes and commentary from leading industry personalities. The authors also discuss: Several new standards on data erasure, including the soon-to-be published standards by the IEEE and ISO How data sanitization strengthens a sustainability or Environmental, Social, and Governance (ESG) program How to adhere to data retention policies, litigation holds, and regulatory frameworks that require certain data to be retained for specific timeframes An ideal resource for ESG, data protection, and privacy professionals, Net Zeros and Ones will also earn a place in the libraries of application developers and IT asset managers seeking a one-stop explanation of how data erasure fits into their data and asset management programs.